Control of the Neutralization Process with the Generic Model Algorithm - Manzi, Joao T.; Odloak, Darci; Langer, Otto-Ulrich (Chemical engineering & technology, 1998)
This paper is concerned with the application of the GMC control algorithm to a pilot plant for the neutralization process of a strong acid‐strong base system. A comparison of the experimental results for GMC with the conventional PI strategy is presented. The stability of GMC is analyzed for the neutralization process using the structured singular value concept. The control of the neutralization process has been studied for several decades but it still remains a challenging problem from a practical point of view. The main difficult problem consists of the severe nonlinearity reflected in the S‐shaped gain curve of the system. Different models and control algorithms have been developed. However, most attempts have proved to be inadequate for practical application.